(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The research aims to determine the efficient investment portfolios for the sectors of the Amman Stock Exchange, and to determine the efficient investment ratios for their sectors, for the period (2004-2021), using quadratic programming, and using the Excel Solver tool. Amman Stock Exchange without this having a significant impact on the size of the risk, In addition to the large variation between sectors in terms of levels of return and risk, which indicates the need to study each sector in terms of aspects related to levels of return and risk associated with it, in order to reach an efficient portfolio. The investor avoids the risks of economic fluctuations in important sectors and exploits the positive results in his interest ,which indicates that the components of the portfolio are directed to the category of assets that include several companies (a sector), and not directed towards a financial asset issued by a particular company, And based on the assumption that the sector index is an important lead stock performance, which results in the combination of assets that are not fully correlated with each other, reduces the risk of portfolio volatility and maximizing potential riskadjusted returns. which means that investors can adopt the quadratic programming method, when His desire to build an efficient investment portfolio that would achieve the highest possible return and less risk, as well as the possibility of using this method to form an efficient portfolio using the Amman Stock Exchange companies for each sector separately, The results also indicate the sensitivity of the return to the investment ratios, as a result of the higher return in greater proportions than the risk, when changing the investment ratios.